A Bibliometric and Visualization Analysis of Intermittent Fasting - Chen, Shiying; Han, Rui; Liu, Haitao (Frontiers in Public Health, 2022)
CiteSpace software was utilized to visually analyze the literature on intermittent fasting from Web of Science from 2000 to 2020 in order to reveal the current status, research hotspots and emerging trends of intermittent fasting. The results show that: (1) intermittent fasting research results are increasing year by year; (2) the United States is at the core of this field and has a high influence; (3) intermittent fasting research is mainly concentrated in the fields of nutrition, cell biology and kinesiology, which embodies interdisciplinary characteristics; (4) the literature of Sutton, Mattson and Trepanowski that were published in the same period have the highest co-citation frequencies, however, their research perspectives are quite different, reflecting that the research in this field is still in a state of continuous development; (5) from the perspective of citation bursts, the evolution of research hotspots in this field in the last 20 years can be divided into 3 stages; (6) the keyword timeline mapping shows that time restricted feeding is at the forefront of this research field. This study can help researchers explore the field for the first time to quickly grasp the frontiers and obtain more valuable data, thereby providing facilitation for the follow-up research.